The participation of art and literature in the discursive construction of a history of education - Gómez i Mundó, Anna (Historia y Memoria de la Educación, 2016)
This article focuses its attention on observing and evaluating the different elements which the arts and literature can contribute to the boundless endeavour of understanding the history of education. This is done by considering the processes of artistic creation together with their expressions not only as documentary sources used for investigation but also as experiences, objects and discourses which open the possibility of recognising and considering certain epistemological and methodological elements of our research. The content is presented in the form of a discussion, exposing those aspects that are relevant to the articulation of a possible discourse of the history of education. Resorting to the relationship existing between the different arts and literature, the author examines and describes her findings, reached through the process of observation, analysis and reflection, working towards the conclusion —always unfinished— which closes the article. In this way a reading of the text leads to the consideration that all research methods —whether aided by the arts and literature or not— may be seen as experiences that contain, create and project an aesthetic.